(untitled) (Historia, 2021)
The police raid on Liliesleaf on 11 July 1963 is understood to be the result of informants within the liberation movements either breaking down in detention or “selling out” and providing information about the farm with its safe house and its people. This paper, while acknowledging that there were informants inside the liberation movements, maintains that this was only a fragment of a kaleidoscope of events culminating in the raid and subsequent Rivonia Trial. Rather it was a covert investigation undertaken since 1962 that resulted in the blow delivered by the combined security agencies, that shattered the underground networks opposing the apartheid state. It was an investigation which relied extensively on the principles of the mythological Greek Trojan horse; it used persons and technology that aimed to undermine and overthrow their opponent, to subvert and defeat it from within, while appearing non-threatening. This paper identifies three Trojan horses. A human spy concealed behind the innocent look of a child who fronted for sinister forces. Electronic warfare deployed by the military and linked to an innocuous caravan park; and finally a laundry van to deliver the surgical knockout strike. Yet all this subterfuge has eluded the narrative for 53 years.